A non-invasive far-red light-induced split-Cre recombinase system for controllable genome engineering in mice - Wu, Jiali (Nat Commun, 2020)
The Cre-loxP recombination system is a powerful tool for genetic manipulation. However, there are widely recognized limitations with chemically inducible Cre-loxP systems, and the UV and blue-light induced systems have phototoxicity and minimal capacity for deep tissue penetration. Here, we develop a far-red light-induced split Cre-loxP system (FISC system) based on a bacteriophytochrome optogenetic system and split-Cre recombinase, enabling optogenetical regulation of genome engineering in vivo solely by utilizing a far-red light (FRL). The FISC system exhibits low background and no detectable photocytotoxicity, while offering efficient FRL-induced DNA recombination. Our in vivo studies showcase the strong organ-penetration capacity of FISC system, markedly outperforming two blue-light-based Cre systems for recombination induction in the liver. Demonstrating its strong clinical relevance, we successfully deploy a FISC system using adeno-associated virus (AAV) delivery. Thus, the FISC system expands the optogenetic toolbox for DNA recombination to achieve spatiotemporally controlled, non-invasive genome engineering in living systems.